Efficacy of biological treatment in inflammatory bowel disease – a single-center experience - Michalak, Agata; Kasztelan-Szczerbinska, Beata; Laskowska, Katarzyna; Radwan, Piotr; Cybulski, Marek; Cichoż-Lach, Halina (Polish Journal of Public Health, 2020)
Introduction. Efficacy of biological treatment (BT) is a key issue among inflammatory bowel disease (IBD) patients. Laboratory markers and endoscopic procedures are basic diagnostic tools in the assessment of response to biological agents in the course of Crohn’s disease (CD) and ulcerative colitis (UC). Aim. The aim of our investigation was to assess the correlation between laboratory parameters and endoscopic picture in the course of BT in patients with IBD – CD and UC –treated with biological agents. Material and methods. The total number of 71 patients were enrolled in the study, 25 with CD and 46 with UC. When it comes to 15 patients with CD, they were treated with infliximab (IFX) and 10 patients with adalimumab (ADA) – one year of therapy. Patients with UC were administered IFX – induction therapy. Laboratory tests (C-reactive protein (CRP) and platelet (PLT) count) and colonoscopy were performed in all patients before and during BT. Results. BT improved endoscopic picture (SES-CD, MAYO) in all patients. BT lowered CRP (p<0.05) and PLT count (p<0.05) in CD group. CRP level and PLT count decreased in UC group, too (p<0.05). A positive correlation between PLT count and SES-CD score prior to the first dose was noticed in ADA group. CRP level correlated positively with PLT count in CD patients treated with IFX before the introduction of BT. Moreover, CRP level correlated positively with both MAYO score and MAYO endoscopic subscore after the second dose of IFX and after finished induction regimen in UC group. Discussion. BT revolutionized a natural history of IBD and its efficacy was approved worldwide. Nevertheless, biological agents do not lead to a full remission of the disease in all patients. Because of this reason, laboratory parameters and endoscopic picture must be carefully monitored during BT to achieve the best outcome in IBD patients. Conclusion. Full clinical and endoscopic remission of IBD was not achieved, although BT lowered CRP level, PLT count and improved endoscopic picture of patients enrolled into our study.